PENINGKATAN HASIL BELAJAR PADA PEMBELAJARAN TEMATIK TERPADU MENGGUNAKAN MODEL THINK PAIR SHARE DI SD - Agustin, Bella; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
The purpose of the research is to describe the implementation and improvement of integrated thematic learning outcomes using the Cooperative type Think Pair Share (TPS) model in grade IV of SDN 24 Talamau Kabupaten Pasaman Barat.. This type of research is classroom action research and uses qualitative and quantitative approaches. This research was conducted on class IV SDN 24 Talamau Kabupaten Pasaman Barat.totaling 10 people consisting of 4 male students and 6 female students. In term of lesson plans, the score increased from 81,8% in cycle I to 95% in cycle II. In term of teacher’s aspect, the score enhanced from 77,5% in cycle I to 95% in cycle II. Meanwhile, in term of the student’s aspect, the score increased from 77,5% in cycle I to 95% in cycle II. The student’s learning outcomes reached a percentage of completeness 60% with an average value of 79 increased in the second cycle percentage of completeness 90% with an average achievement of 90,3.